Strategi Pembelajaran Pendidikan Agama Islam Berbasis Neuroeducation dalam Meningkatkan Pemahaman dan Kecerdasan Spiritual Siswa - Fikri Amrullah; Hidayatullah; Muizzudin; Encep Syaripudin; Wasehudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic Religious Education (PAI) faces challenges in improving students' understanding and spiritual intelligence, especially in the modern era full of distractions. The Neuroeducation approach, based on cognitive neuroscience, offers a more effective learning method by considering how the brain processes information. This strategy integrates multisensory stimulation, emotional engagement, and direct experience to create more meaningful and sustainable learning. This research employs a qualitative case study method, where data is collected through classroom observations, in-depth interviews with teachers and students, and document analysis related to the implementation of the Neuroeducation strategy in PAI. Data analysis was conducted using thematic analysis, with validity strengthened through data triangulation from various sources. The results indicate that the Neuroeducation-based strategy significantly enhances students' understanding of PAI concepts and fosters the development of their spiritual intelligence. Experience-based learning methods, storytelling, and self-reflection proved to be more effective than conventional lecture methods. However, challenges such as teachers' limited understanding and technological infrastructure constraints remain. Therefore, teacher training and the integration of neuroscience-based approaches into the PAI curriculum are necessary to optimize this method’s implementation. With the right approach, Neuroeducation can be an innovative solution to developing a generation of Muslims who are intelligent, well-characterized, and have a deep understanding of religion.